Learning disabilities [videorecording] a complex journey - King, Winnie; Glovach, Dan (Keeping kids healthy, 2005)
If your child has trouble reading or seems to have more difficulty with schoolwork than other students, your child may have a learning disability. This program focuses on what learning disabilities are (neurological problems processing information), how to find out if your child has a learning disability, identifying warning signs for learning disabilities, the benefits of early intervention, dealing with the child's special needs in the schools, developing individualized education programs (IEPs), and where you can go for help